Effect of the App Miro in the achievement of collaborative learning in students of an institute - Morón-Hernández, Julia Liliana (2022)
The research addresses the problems of the students of the Food Industry Program at the Federico Uranga Institute of Public Technological Higher Education, who during the development of their virtual sessions in the course of Fundamentals of research, did not evidence collaborative learning, and it is that they did not apply the ideal technological tools for this purpose, for this reason, the decision was made to apply an Intervening Plan applying didactic strategies and students using digital tools. The objective of the research was to determine the effect of the Miro App on the achievement of collaborative learning in students of the Institute, for this, the positivist paradigm was used, pre-experimental design, the sample was constituted by 28 students of the Food Industry Studies Program. The instrument used was a Likert-type survey which was previously subjected to its validity and reliability. The results obtained using Wilcoxon's statistical T test indicated that there were significant differences between the pretest; where 42.43% was obtained and the intervention program was completed, the postest 94.21%. The general hypothesis was contrasted and a Z=-4.628 was obtained. Which showed that the application of the Miro App favorably influences the achievement of collaborative learning, with statistically significant difference (p<0.05), se logró validar la hipótesis de estudio ya que los logros fueron significativos.